Lexical Errors in EFL Students’ Written Production - Cordero Badilla, Damaris (2020)
This research describes and analyzes common vocabulary errors found in the written production of English as a Foreign Language (EFL) students. Based on the lexical errors identified, the analysis of the data was carried out by adapting James’ lexical error taxonomy and included the written production of 56 students from the Universidad Nacional (Costa Rica). It can be concluded that the participants had more lexical errors in semantics and less at the level of discourse. Recommendations on teaching methodologies to correct lexical errors related issues are included.